Prevalence of Thyroid Disorders in the Patient Visiting Tertiary Care Hospital in Jhapa District, Nepal - Sinha, Amar Kumar; Shah, Tirtha Narayan; Rai, Ujwal (Medical Journal of Eastern Nepal, 2024)
Background Thyroid dysfunction is a leading global endocrine disorder, affecting 30-40% of endocrine patients. Thyroid hormones regulate metabolism, growth, and cardiovascular health. Both hyper- and hypothyroidism are linked to serious health issues. Undiagnosed cases are common, with 42 million affected in India. Screening programs, especially for women, are vital for early detection and treatment. Methods This is a prospective hospital based study was conducted in the central laboratory at B&CMedical College Teaching Hospital and Research Centre Birtamode, Jhapa from March 2022 to January 2023.Venous Blood samples was collected and fT3,fT4 and TSH was estimated by Chemiluminescence Immunoassay (CLIA) method using Backman Coulter Access 2 analyser. Thyroid statuses were categorized as euthyroid, hypothyroid, subclinical hypothyroid, hyperthyroid, and subclinical hyperthyroid based on test results. Results The most common thyroid disorder in female was sub-clinical hypothyroidism (14.7%) and the least common was hypothyroidism (0.8%). The most common thyroid disorders was sub-clinical hypothyroidism (11.8%) and the least common was hypothyroidism (1.2%) in male. Among the thyroid disorders, subclinical hypothyroidism was most prevalent in all the age groups. Hyperthyroidism and its subclinical type (0.6%) were the least prevalent in the age group less than 15 years. Conclusions The prevalence of subclinical hypothyroidism was more significant and it increased with the age. Cross-sectional study comparing with different etiological factors like stress levels, geographic, environment, auto immunity, drugs, iodine status etc. may be required.